2001
DOI: 10.1016/s0022-5347(05)65645-5
|View full text |Cite
|
Sign up to set email alerts
|

Indication, Surgical Technique and Outcome of Orthotopic Renal Transplantation

Abstract: Despite the technical challenges, orthotopic renal transplantation in patients with unsuitable pelvic vessels can result in excellent patient and graft survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Open surgery for orthotopic kidney transplant has been reported in the literature as an effective alternative for those recipients in whom a heterotopic transplant was inappropriate, such as patients with a retained iliac fossa from a former graft, thrombosis of the iliac vein, or severe arthromatosis on the iliac artery. [15][16][17][18] The long-term patient and graft survival rates are comparable with those for conventional heterotopic kidney transplant. 18 However, open orthotopic kidney transplant has not been the favored approach because it is more difficult when compared with conventional heterotopic kidney transplant.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Open surgery for orthotopic kidney transplant has been reported in the literature as an effective alternative for those recipients in whom a heterotopic transplant was inappropriate, such as patients with a retained iliac fossa from a former graft, thrombosis of the iliac vein, or severe arthromatosis on the iliac artery. [15][16][17][18] The long-term patient and graft survival rates are comparable with those for conventional heterotopic kidney transplant. 18 However, open orthotopic kidney transplant has not been the favored approach because it is more difficult when compared with conventional heterotopic kidney transplant.…”
Section: Discussionmentioning
confidence: 87%
“…It usually requires a longer midline incision or use of a posterolateral lumbotomy, in which massive muscles will be cut. 17,18 As a result, more analgesia is required and the recovery takes longer. This study has shown that orthotopic kidney transplant can be performed safely by a laparoscopic ap- proach, in which only a small midline (6-cm) incision is needed.…”
Section: Discussionmentioning
confidence: 99%
“…It usually requires a longer midline incision or use of a posterolateral lumbotomy, in which massive muscles will be cut. 17,18 As a result, more analgesia is required and the recovery takes longer. This study has shown that orthotopic kidney transplant can be performed safely by a laparoscopic approach, in which only a small midline (6-cm) incision is needed.…”
Section: Discussionmentioning
confidence: 99%
“…The anastomosis of graft vessels in our patient to the lower abdominal aorta and vena cava was impossible due to extensive atheromatosis and venous thrombosis. Under these conditions an orthotopic kidney transplantation with anastomosing donor and recipient native vessels is well established [35] and had been previously performed in patients with an aortic occlusion, severe pelvic atherosclerosis, pelvic vascular anomaly, previews kidney transplantation, and urinary tract reconstruction [6]. …”
Section: Discussionmentioning
confidence: 99%